Dispatches from Puerto Nowhere : an American story of assimilation and erasure - Lopez, Robert, 1971- (TwoDollarRadio, 2023)
"Robert Lopez's grandfather Sixto was born in Mayaguez, Puerto Rico, in 1904, immigrating to the United States in the 1920s, where he lived in a racially proportioned apartment complex in East New York, Brooklyn, until his death in 1987. The family's efforts to assimilate within their new homeland led to the near complete erasure of their heritage, culture, and language within two generations. Through family recollection, the constant banter volleyed across nets within Brookly's diverse tennis community, as well as an imagined fabulist history drawn from Sixto's remembered traits, Robert Lopez paints a haunting, compassionate, and tremendously moving portrait of family that attempts to bridge the past to the present, and re-claim a heritage threatened by assimilation and erasure."--